2019
DOI: 10.1002/anie.201813968
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Route to Nonlinear Optical Materials: Three‐Site Aliovalent Substitution Involving One Cation and Two Anions

Abstract: Tw om ixed-metal gallium iodate fluorides,n amely, a-and b-Ba 2 [GaF 4 (IO 3 ) 2 ](IO 3 )(1 and 2), have been designed by the aliovalent substitutions of a-a nd b-Ba 2 [VO 2 F 2 (IO 3 ) 2 ]-(IO 3 )( 3 and 4)i nvolving one cationic and two anionic sites. Both 1 and 2 display large second-harmonic generation responses ( % 6 KH 2 PO 4 (KDP)), large energy band gaps (4.61 and 4.35 eV), wide transmittance ranges ( % 0.27-12.5 mm), and high relevant laser-induced damage thresholds (29.7 and 28.3 AgGaS 2 ,r espective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
133
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(136 citation statements)
references
References 58 publications
3
133
0
Order By: Relevance
“…Laser‐induced‐damage‐threshold (LIDT) experiments showed that CsVO 2 F(IO 3 ) has a very large LIDT value of 107.9 MW cm −2 , which is about 50 times of that of AgGaS 2 (AGS; 2.22 MW cm −2 ). This value is also larger than that of α‐Ba 2 [GaF 4 (IO 3 ) 2 ](IO 3 ) (63.35 MW cm −2 ) . We suggest that the novel 3D anionic framework is favorable to enhance the LIDT value.…”
Section: Figurementioning
confidence: 66%
See 2 more Smart Citations
“…Laser‐induced‐damage‐threshold (LIDT) experiments showed that CsVO 2 F(IO 3 ) has a very large LIDT value of 107.9 MW cm −2 , which is about 50 times of that of AgGaS 2 (AGS; 2.22 MW cm −2 ). This value is also larger than that of α‐Ba 2 [GaF 4 (IO 3 ) 2 ](IO 3 ) (63.35 MW cm −2 ) . We suggest that the novel 3D anionic framework is favorable to enhance the LIDT value.…”
Section: Figurementioning
confidence: 66%
“…Under laser‐generating radiation at 2.05 μm (Figure ), CsVO 2 F(IO 3 ) exhibits a strong SHG signal 1.1 times as intense as KTP (particle size 150–210 μm), which is type‐I phase‐matchable. It is obviously larger than those of α‐ and β‐Ba 2 [VO 2 F 2 (IO 3 ) 2 ](IO 3 ) (0.7 times that of KTP) and α‐ and β‐Ba 2 [GaF 4 (IO 3 ) 2 ](IO 3 ) (0.4 times that of KTP) measured under the same experimental conditions; all of them contain the 0D Λ‐shaped cis ‐[MO x F y (IO 3 ) 2 ] n − building units.…”
Section: Figurementioning
confidence: 85%
See 1 more Smart Citation
“…[14,18,[37][38] Another effective strategy that has been widely recognized to realize wide band gap is to introduce F À into iodates, which has led to a series of F À -containing iodates with large band gaps, such as Bi(IO 3 )F 2 (3.97 eV), and α-Ba 2 [GaF 4 (IO 3 ) 2 ]IO 3 (4.61 eV). [19,39] The existence of F À can shorten the optical cutoff edge and even alter the birefringence property of iodate compounds. 39 Therefore, investigation in the fifth periodic d 0 À TM (Zr 4 + , Nb 5 + )containing iodates system can be very meaningful in exploring iodate crystals with wide band gap; further introducing F À into MÀ d 0 À TM (Zr 4 + , Nb 5 + )À IO 3 is very likely to enlarge the band gap of the iodate compounds.…”
Section: Introductionmentioning
confidence: 99%
“…However, the reported materials in deep‐ultraviolet (DUV) and mid and far‐infrared (MFIR) regions are unable to meet market requirements. Even though a variety of NLO materials have been developed in this regard, exploring new suitable NLO materials with NCS structures in these spectrum regions remains a major challenge, and it is also a hot topic in the field of inorganic solid state chemistry.…”
Section: Introductionmentioning
confidence: 99%